Significance of Fecal Coliform-Positive Klebsiella - Bagley, Susan T. (1977)
A total of 191 Klebsiella pneumoniae isolates of human clinical, bovine mastitis, and a wide variety of environmental sources were tested for fecal coliform (FC) response with the membrane filtration and most probable number techniques. Twenty-seven Escherichia coli cultures of human clinical and environmental origins were also tested. Eighty-five percent (49/58) of known pathogenic K. pneumoniae were FC positive, compared with 16% (19/120) of the environmental strains. E. coli results indicated 93% (13/14) of the clinical and 85% (11/13) of the environmental strains as FC positive. There was no significant difference in the incidence of FC-positive cultures between pathogenic Klebsiella and E. coli. pH measurements of K. pneumoniae and E. coli cultures growing in m-FC broth at 44.5°C revealed three distinct pH ranges correlating with colony morphology. β-Galactosidase assays of Klebsiella and E. coli cultures at 44.5°C indicated all were able to hydrolyze lactose, even if they were FC negative by the membrane filtration or most probable number techniques. The FC response pattern appears stable in K. pneumoniae. Three pathogenic cultures showed no change in FC responses after 270 generations of growth in sterile pulp mill effluent. Since K. pneumoniae is carried in the gastrointestinal tract of humans and animals and 85% of the tested pathogenic strains were FC positive, the isolation of FC-positive Klebsiella organisms from the environment would indicate their fecal or clinical origin or both. The added fact that K. pneumoniae is an opportunistic pathogen of increasing importance makes the occurrence of FC-positive environmental Klebsiella, particularly in large numbers, a potential human and animal health hazard.